Measurement and analysis on the sensitization behavior of SS-304 welds using Nb-based stabilization through flux-coated gas tungsten arc welding. (September 2019) - Singh, Chitkarnvir; Kumar, Harmesh; Kumar, Rajesh
The objective of this research work is to enhance the microstructure and intergranular corrosion resistance of AISI 304 stainless steel by diffusing the stabilizing element, that is, Niobium (Nb), using a comparatively new methodology termed as flux-coated gas tungsten arc welding. In this process, a suitable material in powder form (pure Nb powder of size < 20 μm) is mixed with acetone and then coated on the V-joint of the plates before welding. The welded joint's surface microstructure and chemistry have been analyzed by optical microscopy, scanning electron microscopy and energy-dispersive x-ray spectroscopy. The microstructural results demonstrate that the diffusion of Nb changes the ferrite morphology of the weld joint to lathy ferrite from vermicular ferrite because of an increase in supercooling during solidification. The results of the investigations indicate that the flux-added weldments exhibited 26 HV more microhardness than conventional welded weldments in the fusion zone. Furthermore, the corrosion behavior of both gas tungsten arc welding–treated and flux-coated gas tungsten arc welding–treated weldments has been evaluated by the double-loop electrochemical potential kinetic reactivation test. The latter revealed that Nb-diffused weldment features insulative and protective properties and displays zero degree of sensitization, whereas conventional welded weldment gives a degree of sensitization of 2.53.